Opsin 1 and Opsin 2 of the Corn Smut Fungus Ustilago maydis Are Green Light-Driven Proton Pumps - Panzer, Sabine; Brych, Annika; Batschauer, Alfred; Terpitz, Ulrich (Frontiers in Microbiology, 2019)
In fungi, green light is absorbed by rhodopsins, opsin proteins carrying a retinal molecule as chromophore. The basidiomycete Ustilago maydis, a fungal pathogen that infects corn plants, encodes three putative photoactive opsins, called ops1 (UMAG_02629), ops2 (UMAG_00371), and ops3 (UMAG_04125). UmOps1 and UmOps2 are expressed during the whole life cycle, in axenic cultures as well as in planta, whereas UmOps3 was recently shown to be absent in axenic cultures but highly expressed during plant infection. Here we show that expression of UmOps1 and UmOps2 is induced by blue light under control of white collar 1 (Wco1). UmOps1 is mainly localized in the plasma membrane, both when expressed in HEK cells and U. maydis sporidia. In contrast, UmOps2 was mostly found intracellularly in the membranes of vacuoles. Patch-clamp studies demonstrated that both rhodopsins are green light-driven outward rectifying proton pumps. UmOps1 revealed an extraordinary pH dependency with increased activity in more acidic environment. Also, UmOps1 showed a pronounced, concentration-dependent enhancement of pump current caused by weak organic acids (WOAs), especially by acetic acid and indole-3-acetic acid (IAA). In contrast, UmOps2 showed the typical behavior of light-driven, outwardly directed proton pumps, whereas UmOps3 did not exhibit any electrogenity. With this work, insights were gained into the localization and molecular function of two U. maydis rhodopsins, paving the way for further studies on the biological role of these rhodopsins in the life cycle of U. maydis.